Maternal serum unmetabolized folic acid concentration following multivitamin and mineral supplementation with or without folic acid after 12 weeks gestation: A randomized controlled trial - Dian C. Sulistyoningrum; Thomas R. Sullivan; Monika Skubisz; Debra J. Palmer; Simon Wood; Per Magne Ueland; Adrian McCann; Maria Makrides; Timothy J. Green; Karen P. Best (Wiley, 2024)
Abstract Pregnant women are advised to take folic acid (FA) supplements before conception and during the first trimester of pregnancy. Many women continue FA supplementation throughout pregnancy, and concerns have been raised about associations between excessive FA intake and adverse maternal and child health outcomes. Unmetabolized folic acid (UMFA) is found in serum after high FA intakes and is proposed as a biomarker for excessive FA intake. We aimed to determine if removing FA from prenatal micronutrient supplements after 12 weeks of pregnancy reduces serum UMFA concentrations at 36 weeks gestation. In this double‐blind, randomized controlled trial conducted in South Australia, 103 women with a singleton pregnancy were randomly assigned at 12-16 weeks gestation to take a micronutrient supplement containing no FA or 800 µg/day FA from enrollment until 36 weeks gestation. Ninety women (0 µg/day FA n = 46; 800 µg/day FA n = 44) completed the study. Mean, UMFA concentration was lower in the women randomized to the 0 µg/day group compared to the 800 µg/day FA group, 0.6 ± 0.7 and 1.4 ± 2.7 nmol/L, respectively. The adjusted mean difference (95% CI) in UMFA between the groups was [‐0.85 (−1.62, −0.08) nmol/L, p = 0.03]. Maternal serum and red blood cell folate concentrations were lower in the 0 µg/day FA group than in the 800 µg/day group (median 23.2 vs. 49.3 and 1335 vs. 1914 nmol/L, respectively; p < 0.001). Removing FA at 12-16 weeks gestation from prenatal micronutrient supplements reduced the concentration of UMFA at 36 weeks gestation.